Problem-Solving on Coastal Environmental Issues: A Study of Pre-Service Biology Teachers' Competencies - Pradana, Sendy Putra; Antony, Muhammad Khoirul; Ramadhan, Ahmad Naharuddin; Sianturi, Advend Sri Rizki (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the problem-solving abilities of pre-service biology teachers in addressing coastal environmental issues through a Higher Order Thinking Skills (HOTS) approach. The research employed a descriptive method, using tests and interviews as data collection techniques. The HOTS-based test was administered to students enrolled in the Environmental Education course at Pattimura University. The test instrument was developed based on five problem-solving indicators: problem identification, problem analysis, formulation of alternative solutions, evaluation of solutions, and decision-making including follow-up planning. In addition to the test, unstructured interviews were conducted to explore students' perceptions of the questions and the challenges they encountered. The results showed an average student score of 74.0, with the highest score in problem identification (84), followed by problem analysis (76), solution evaluation (74), alternative solution formulation (72), and the lowest in decision-making and follow-up actions (64). These findings suggest that while students demonstrated strong abilities in identifying and analyzing coastal environmental problems, their capacity to design practical and implementable solutions requires further development. The outcomes of this study provide a foundation for developing a more context-based curriculum in Ambon that addresses local coastal environmental issues.